Biostratigraphy of the Upper Cretaceous for selected sections in northern Iraq - Abdallah, Fatima Talib; Al-Dulaimi, Salam I. (Iraqi Journal of Science, 2019)
The Aqra - Bekhme, Shiranish, Tanjero and Kolosh formations outcrop in the High Folded Zone, Northern Iraq in Erbil and Sulaymaniyah governorates. The formations have been studied at two selected geological sections (Bekhme Gorge and Zarda Bee). In this study, these formations are investigated based on both benthic and planktonic foraminifera. Depending on foraminifer’s investigation, three biozones have been recognized; two biozones are identified in the benthic foraminifera and the third one is identified in the planktonic foraminifera as follow: Siderolites calcitropodes - Orbitoides apiculatus - Omphalocyclus macroporus Assemblage zone. Loftusia morgani range zone. Abathomphalus mayaroensis rangezone.